Three forms of gonadotropin-releasing hormone (GnRH) in brain and pituitary of Asian seabass Lates calcarifer (Bloch, 1790) analysed by high performance liquid chromatography combined with time-resolved flouroimmunoassay and immunohistochemistry - Xuan Pham, Ky; Amano, Masafumi; Amiya, Noriko; Viet Dao, Ha; Van Vo, Quang (Indian Journal of Fisheries, 2016)
Three forms of gonadotropin-releasing hormone (GnRH) namely, salmon GnRH (sGnRH), chicken GnRH-II (cGnRH-II) and seabream GnRH (sbGnRH) were identified in the brain of Asian seabass Lates calcarifer using reverse-phase high performance liquid chromatography (rpHPLC) combined with time-resolved fluoroimmunoassay (TR-FIA) using rabbit polyclonal antibody raised against sGnRH, cGnRH-II and sbGnRH. An extract of L. calcarifer brain showed a similar retention time to that of synthetic sGnRH, cGnRH-II and sbGnRH on rpHPLC. In the brain, cGnRH-II and sGnRH levels were high, whereas sbGnRH was absolutely dominant in the pituitary. In addition, cGnRH-II, sGnRH and sbGnRH immunoreactive (ir) cell bodies and fibers in the brain and pituitary were also examined by immunohistochemistry. sGnRH-ir cell bodies were localised in the ventromedial part of the rostral olfactory bulb, terminal nerve ganglion region, and the transitional area between the olfactory bulb and telencephalon. cGnRH-II-ir cell bodies were located only in the midbrain tegmentum and sbGnRH-ir cell bodies were evident in the preoptic area. sGnRH-ir fibers were distributed throughout the brain, especially abundant in the forebrain. cGnRH-II-ir fibers were found in many parts of the brain, being more dense in the midbrain, whereas sbGnRH-ir fibers were localised in the preoptic-hypothalamic area, innervating the pituitary. In the pituitary, sbGnRH-ir fibers were profuse in the neurohypophysis and invaded the proximal pars distalis. These results confirm the existence of multiple GnRH forms with different physiological roles in L. calcarifer. Among them, sbGnRH is considered to be the best candidate for pituitary regulation while sGnRH and cGnRH-II can function as neurotransmtters or as neuromodulators in this species.